THE POWER OF ENERGIZER ACTIVITIES IN THE CLASSROOM - Murodova Ruxsora Otabekovna; Mamatova Zulfira Faziqulovna; Gopurova Nargiza Avazbekovna (XALQARO ILMIY-AMALIY ANJUMAN "TA’LIM MAYDONI TENDENSIYALARI: KOMPETENTSIYALAR, INNOVATSIYALAR VA TEXNOLOGIYALAR", 2025)
This article explores the concept, categorization, and implementation of energizer activities in educational settings, emphasizing their role in enhancing learner engagement, cognitive focus and classroom interaction. Energizers are short, interactive tasks designed to revitalize students physically, mentally, creatively or socially. The article delienates four main types of energizers- physical, mental, creative and social - each with distinct functions and pedagogical value. It further outlines best practices for the effective integration of these activities.